Spontaneous Regression of De Novo Cavernous Malformation in the Spinal Canal after Hemorrhage: A Case Report - Saura, Minami; Yanaka, Kiyoyuki; Onuma, Kuniyuki; Nakamura, Kazuhiro; Takahashi, Nobuyuki; Marushima, Aiki; Ishikawa, Eiichi (Asian Journal of Neurosurgery, 2025)
Spinal cavernous malformations are rare vascular malformations with an unclear natural history, especially in de novo cases without prior radiation exposure or genetic predisposition. Although surgery is often recommended for symptomatic hemorrhagic lesions, spontaneous regression is extremely rare. A 74-year-old man presented with isolated neck pain after a minor head trauma. Computed tomography revealed a hyperdense lesion in the C2 spinal canal, and magnetic resonance imaging (MRI) showed a 16 × 9 × 20 mm intradural, intramedullary mass with protruding extramedullary hemorrhagic features, consistent with a cavernous malformation. A previous MRI 1 year earlier showed no abnormalities, confirming its de novo nature. Surgery was initially planned due to the risk of rebleeding. However, the patient's symptoms resolved spontaneously. A follow-up MRI 9 days later revealed significant regression, with continued involution observed over 5 years. This is the first reported case of spontaneous regression of a de novo spinal cavernous malformation, suggesting that in selected patients, conservative management with serial imaging may be safe in asymptomatic or minimally symptomatic patients showing early regression. Possible mechanisms include hematoma resorption, vascular thrombosis, or cerebrospinal fluid mediated clearance. Further studies are needed to identify predictive factors for regression and refine treatment strategies.
Keywords: cavernous malformation; de novo formation; hemorrhage; regression; spine